Emergent Paradigm: Critical Realism and Transformative Research in Educational Administration - Egbo, Benedicta (McGill Journal of Education / Revue des sciences de l'éducation de McGill, 2006)
ABSTRACT. This paper explores the prospects of using critical realism as a guidingphilosophy for critical inquiry in the field of educational administration.A relatively recent philosophy in the social sciences, critical realism offers analternative framework for researchers engaged in empirical work that is aimedat transforming undesirable social realities. As a philosophical framework,critical realism recognizes the importance of agency in research and sees socialtransformation as an essential outcome of research in the human sciences.LE PARADIGME EMERGEANT :RÉALISME CRITIQUE ET RECHERCHES TRANSFORMATIVES EN ADMINISTRATION SCOLAIRE.RÉSUMÉ. Ce document explore les possibilités de l’utilisation du réalismecritique comme une philosophie conductrice pour une interrogation critiquedans le secteur de l’administration en éducation. Une philosophie récenteen science sociale, le réalisme critique offre une alternative de démarche detravail pour des chercheurs engagés dans un travail empirique qui est destinéà transformer des réalités sociales indésirables. Comme démarche philosophique,le réalisme critique reconnaît les agencements en recherche et voitles transformations sociales comme des résultats de recherche essentiels ensciences humaines.